JURIDICAL REVIEW OF THE ROLE OF THE SOCIAL OFFICE OF WOMEN'S EMPOWERMENT AND CHILD PROTECTION OF TULUNGAGUNG REGENCY IN PROVIDING PROTECTION TO WOMEN AND CHILDREN - Widowati; Subadi (The Islamic Education and Multiculturalism Foundation, 2023)
To be able to understand the understanding of childhood itself can be seen from various aspects of life so that it approaches the correct meaning, namely religious, economic, sociological, and legal aspects. Therefore, we want to focus on the implementation of the role of Social Service and the Empowerment of Women and Children of Tulungagung Regency Number 23 of 2017 concerning the Implementation of Women and Children Protection. The normative legal research method is one of the approaches used in legal research to analyze applicable legal regulations. This method focuses on analyzing legal sources, such as laws and regulations, court decisions, and other legal documents. Normative legal research methods make an important contribution to understanding and analyzing applicable legal regulations. This approach helps in building a solid legal argument, providing a deeper understanding of the existing legal framework. the role of Social Services and Women Children Empowerment and Women Children Empowerment and Women and Children Empowerment in this context: 1. Policy formulation: 2. Program coordination and implementation 3. Supervision and monitoring: 4. Service and assistance. 5. Education and socialization: The Social Office of Women's Empowerment and Child Protection only makes efforts to resolve reported cases of violations of children's rights 2) its role as a concept that the Social Office of Women's Empowerment and Child Protection of child victims of violence has run quite well by meeting existing standard operating procedures.